Effects of Cu and WS2 addition on microstructural evolution and tribological properties of self-lubricating anti-wear coatings prepared by laser cladding. (May 2021) - Yuan, Jianhui; Yao, Yangguang; Zhuang, Mingxiang; Du, Yeyuan; Wang, Liang; Yu, Zhishui
Abstract: High manganese steel (30CrMnSi) is usually used to prepare the components which works under a high load for long time. In order to extend its service life, the high manganese steel covered with NiCr/TiC, NiCr/TiC–Cu or NiCr/TiC-Cu-WS2 coatings are prepared using laser cladding technology. The influence of Cu and WS2 to the microstructure, hardness and wear performance of the coatings is discussed. The tribological properties of the resulting coatings is evaluated under 100 N in atmosphere environment. The hardness of NiCr/TiC coating is about 3.5 times of that of the substrate owing to the existence of TiC in coating. Due to the addition of Cu, the wear loss of the NiCr/TiC–10%Cu coatings reduces. Furthermore, as the synergistic lubrication of Cu, CrS and WS2, the wear resistance of the NiCr/TiC–10%Cu–10%WS2 coatings are significantly improved. The wear scar width and friction coefficient of the NiCr/TiC–10%Cu–10%WS2 coatings are only 50% of the substrates. And the wear mechanism of this kind of coatings is mainly micro-plough wear. The laser clad self-lubricating anti-wear coating will be one of the most important candidates for its excellent tribological performance. Graphical abstract: Image 1 Highlights: The NiCr/TiC-10%Cu-10%WS2  coating obtained the best friction property among all the coatings in this work. The wear mechanism of coatings containing Cu and WS2  was micro-plough wear.